Penguatan Politik Dan Manajemen Organisasi untuk Meningkatkan Kecakapan Pemuda Melalui Komunikasi dan Forming - Ardian, Muhammad; Kesuma Nasution, Indra; Hazzah Nur R, Siti; Suhendri, Suhendri (PELITA NUSA TENGGARA, 2025)
Strengthening youth as agents of change within the context of democracy and organization is an urgent need to create a more engaged and empowered society. This program aims to enhance political understanding, communication skills, and leadership character among the youth of Ranting IPK PB Selayang I. The methods used include interactive training and workshops encompassing three main components: the formation of political understanding through discussions and political simulations, the development of communication skills through practical exercises, and the building of leadership character through mentoring and leadership activities. Evaluation is conducted through interviews, surveys, and observations before and after the training. The results show that the integration of political understanding and communication skills within the community service program is effective in enhancing the political understanding and engagement of the youth. This community service program successfully creates youth who are more skilled, knowledgeable, and active in society. Strengthening political understanding, communication skills, and leadership character is an effective strategy to shape youth into smart and good citizens.